A design thinking framework for circular business model innovation - Eva Guldmann; Nancy Bocken; H. Brezet (Journal of Business Models (JOBM), 2019)
Purpose: Circular business model innovation (CBMI) can support sustainable business transitions, but the process is poorly understood and there is a lack of tools to assist companies in CBMI. This article aims to contribute to closing this gap by developing a framework for CBMI based on a design thinking approach, which can support the CBMI process. Design: The CBMI framework was derived from a multiple case study in which six case companies created circular business models in collaboration with the researchers. The CBMI processes were studied from the time when circular economy and circular business models were first introduced to the companies and the following six months to two years. Findings: A design thinking process typically consists of three innovation spaces, an exploratory, an ideation, and a prototyping and testing space. Yet, based on the empirical data, this paper identifies two additional spaces, an introductory and an alignment space, for CBMI. The results derived from the six case companies indicate that the developed framework including its tools and techniques are useful for CBMI. Practical Implications: This study contributes with a framework to help practitioners facilitate and manoeuvre the challenging CBMI process. The framework provides guidelines for the CBMI process and inspiration for tools that could be applied flexibly depending on the organisational setting. Value: The main contributions of the paper are: an empirically grounded framework to assist CBMI; deeper insight into the use of design thinking for CBMI; a number of tools to support CBMI more generally; and a better understanding of the stages and activities of a CBMI process.
Keywords: 650; Circular economy; Circular business models; Sustainable business models; Circular business model innovation; Design thinking